THE MODERN TRENDS IN REPRODUCTIVE HEALTH AND REPRODUCTIVE BEHAVIOR OF THE FEMALE POPULATION IN RUSSIA - Валентина Сергеевна Гладкая; Вера Людвиговна Грицинская; Надежда Николаевна Медведева (The Publishing House Medicine and Enlightenment, 2017)
This review summarizes research on the factors affecting the implementation of the reproductive capacity of women by childbearing age in the Russian Federation. The relevance of research due to the fact that Russia is characterized by a narrowed type of the population reproduction and demographic aging. Despite the strengthening in recent years of measures of social support for mothers, there is not provided even a simple reproduction of the population. The program of state demographic policy in the 2007-2025 biennium priorities recognized by reducing the level of reproductive losses, strengthening of reproductive health and research reserves increase fertility. During the implementation of the program noted the positive dynamics of reproductive losses: reducing maternal and 4 times the infant mortality rate is 2,5 times through the creation of federal prenatal centers and routing development of care for women with complicated pregnancy and extra genital pathology. However, there remain significant reproductive losses due to spontaneous miscarriages in time before 22 weeks of pregnancy and the losses associated with impaired fertility. A serious problem for the implementation of the reproductive function is a violation of becoming menstrual functions at teenagers on a background of a disharmonious physical development; early sexual activity, high promiscuity, low contraceptive. Among the social causes that have a negative impact on fertility, marked a change of the current generation of family values in the material well-being, career and setting of the delayed the child birth. It puts forward the proposal to establish regional centers provide comprehensive preventive, rehabilitative, recreational, informational and educational work and social-legal counseling of the female population.